Intrinsic features of Zika Virus non-structural proteins NS2A and NS4A in the regulation of viral replication. - Yufeng Yu; Chengfeng Gao; Chunxia Wen; Peng Zou; Xian Qi; Carol J Cardona; Zheng Xing (Public Library of Science (PLoS), 2022)
Zika virus (ZIKV) is a mosquito-borne flavivirus and can cause neurodevelopmental disorders in fetus. As a neurotropic virus, ZIKV persistently infects neural tissues during pregnancy but the viral pathogenesis remains largely unknown. ZIKV has a positive-sense and single-stranded RNA genome, which encodes 7 non-structural (NS) proteins, participating in viral replication and dysregulation of host immunity. Like those in many other viruses, NS proteins are considered to be products evolutionarily beneficiary to viruses and some are virulence factors. However, we found that some NS proteins encoded by ZIKV genome appeared to function against the viral replication. In this report we showed that exogenously expressed ZIKV NS2A and NS4A inhibited ZIKV infection by inhibiting viral RNA replication in microglial cells and astrocytes. To understand how viral NS proteins suppressed viral replication, we analyzed the transcriptome of the microglial cells and astrocytes and found that expression of NS4A induced the upregulation of ISGs, including MX1/2, OAS1/2/3, IFITM1, IFIT1, IFI6, IFI27, ISG15 or BST2 through activating the ISGF3 signaling pathway. Upregulation of these ISGs seemed to be related to the inhibition of ZIKV replication, since the anti-ZIKV function of NS4A was partially attenuated when the cells were treated with Abrocitinib, an inhibitor of the ISGF3 signaling pathway, or were knocked down with STAT2. Aborting the protein expression of NS4A, but not its nucleic acid, eliminated the antiviral activity of NS4A effectively. Dynamic expression of viral NS proteins was examined in ZIKV-infected microglial cells and astrocytes, which showed comparatively NS4A occurred later than other NS proteins during the infection. We hypothesize that NS4A may possess intrinsic features to serve as a unique type of pathogen associated molecular pattern (PAMP), detectable by the cells to induce an innate immune response, or function with other mechanisms, to restrict the viral replication to a certain level as a negative feedback, which may help ZIKV maintain its persistent infection in fetal neural tissues.